Comparison of outcome of botulinum toxin injection with and without glyceryl trinitrate in chronic anal fissure in terms of post operative pain and healing - Hussain, Shabeer; Ammar , Ahmed Siddique; Hameed, Ahmed Raza; Aslam, Imran; Afzal, Ameer (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the outcome of botulinum toxin injection with and without glyceryl trinitrate with respect to postoperative pain and healing in the treatment of anal fissures. Method: The prospective, comparative study was conducted at the Department of General Surgery, Mayo Hospital, Lahore, Pakistan, from September 1, 2021, to August 31, 2022, and comprised adult chronic anal fissure patients of either gender. They were randomised using the lottery method into group A which received botulinum toxin injection, and group B which received botulinum toxin injection plus 1g of 0.2% topical glyceryl trinitrate cream. Post-operative pain was measured 24 hours after the procedure using the visual analogue scale. Healing was assessed by examining the wound for the appearance of granulation tissue 4 weeks post-procedure. Data was analysed using SPSS 26. Results: Of the 88 patients, 44(50%) were in group A; 32(72.7%) males and 12(27.3%) females with mean age 33.91±14.8 years. There were 44(50%) patients in group B; 35(79.5%) males and 9(20.5%) females with mean age range 36.33±14.9 years. The mean postoperative pain at 24 hours in group A was 4.67±1.16 and it was 3.06±0.65 in group B (p=0.009). In group A, 23(69.7%) patients showed complete healing at 4 weeks compared to 30(90.9%) in group B (p=0.030). Conclusion: Botulinum toxin injection with glyceryl trinitrate could be considered as first line of treatment for chronic anal fissure in patients who refuse surgery and with previous sphincter surgery. Key Words: Anal fissure, Lateral internal anal sphincterotomy, Botulinum toxin injection, Glyceryl trinitrate, Granulation tissue.